Modeling Neuroregeneration and Neurorepair in an Aging Context: The Power of a Teleost Model - Van houcke, Jolien; Mariën, Valerie; Zandecki, Caroline; Seuntjens, Eve; Ayana, Rajagopal; Arckens, Lutgarde (Frontiers in Cell and Developmental Biology, 2021)
Aging increases the risk for neurodegenerative disease and brain trauma, both leading to irreversible and multifaceted deficits that impose a clear societal and economic burden onto the growing world population. Despite tremendous research efforts, there are still no treatments available that can fully restore brain function, which would imply neuroregeneration. In the adult mammalian brain, neuroregeneration is naturally limited, even more so in an aging context. In view of the significant influence of aging on (late-onset) neurological disease, it is a critical factor in future research. This review discusses the use of a non-standard gerontology model, the teleost brain, for studying the impact of aging on neurorepair. Teleost fish share a vertebrate physiology with mammals, including mammalian-like aging, but in contrast to mammals have a high capacity for regeneration. Moreover, access to large mutagenesis screens empowers these teleost species to fill the gap between established invertebrate and rodent models. As such, we here highlight opportunities to decode the factor age in relation to neurorepair, and we propose the use of teleost fish, and in particular killifish, to fuel new research in the neuro-gerontology field.